Discharge Education for Mild Traumatic Brain Injury Patients at Emergency Department - Songwathana, Praneed; Nurhayati, Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to review the literature on educational interventions for the discharge of mild traumatic brain injury (mTBI) patients in the Emergency Room (IGD). Database searches were performed based on PICO queries and keywords. using ProQuest, ScienceDirect, Scopus, and PubMed for the period 2012-2019. Ten studies were reviewed. The findings revealed the contents of discharge information for mTBI patients including diagnosis, signs and symptoms, treatment and medication, pain management, home care, and ED return instructions. Four methods of discharge intervention are commonly used in the ED; written, spoken, animated and moving videos, and printed instructions measured over two time periods, either pre-discharge in the ED or follow-up 1-2 weeks post-discharge at home. In conclusion, combined teaching was more effective in terms of level of knowledge, understanding, and ED repeat visits. Keywords: Discharge education, Emergency, Minor Traumatic Brain Injury